Observations of the Onset of the Energy Quench in ASDEX Upgrade Density Limit Disruptions - G. Pautasso (2002)
Tokamak major density limit disruptions are usually preceded by a m/n=2/1 tearing mode, that may or may not lock to the vessel wall. The complete destruction of energy confinement in these major disruptions is known to have a characteristic m/n=1/1 form. Initially only a small degradation of the confinement occurs, as is observed by the slow increase of the electron temperature at the plasma edge. But at some stage of the evolution of the 2/1 mode the degradation of the energy confinement shows an abrupt increase that quickly leads to a cold plasma. It was observed in circular plasmas that this abrupt increase of the degradation of the energy confinement starts at the low field side, in the neighborhood of the core facing side of the O point of the 2/1 mode. At this position a region with electron temperature similar to the temperature in the 2/1, O point, is observed to expand quickly towards the plasma core. Thomson scattering showed that at the time the electron temperature profile is flat over the plasma radius, the electron density is ~ 50% higher inside the 2/1 mode, compared at the onset of the 2/1, O point T_e erosion. In this paper we report on the 2/1, O point T_e erosion that we also observed in ASDEX Upgrade major density limit disruptions. The evolution of the temperature profile is measured with a heterodyne radiometer with 60 channels and 32 μ s time resolution. We plan to investigate also the evolution of the density profile both from the high field side and from the low field side, measured with broad band multi channel reflectometer with 35 μ s time resolution. The observation of the density increase inside the 2/1 mode associated with the already observed 2/1, O point T_e erosion will be an important indication that convection is involved in the abrupt destruction of the energy confinement, characteristic of major density limit disruptions.